Виды библиотечой деятельности ЮНЕСКО - Macevičiūtė, Elena (Knygotyra, 1988)
The aim of the article is to classify the activities of UNESCO in the field of library work. The main types of these activities are singled out based on the criteria of main functions of international organizations: • Governing Activities: These are carried out by determining the main principles of library activities and announcing them in declarations, programs, projects, and other documents. This includes stating the rules in various fields of library work and implementing them through international conventions, as well as creating concepts for the development of libraries at both national and international levels. • Controlling Activities: These are carried out by: • Stating the existing status. • Comparing it with the rules and ideal models. • Declaring responsibility for deviations from them. The task is performed by collecting library statistics and other information. This is a major aspect of the work of international organizations. The evaluation of activities in librarianship is formulated as recommendations by UNESCO. • Performing Activities: These involve UNESCO directly engaging in library work by sending experts to organize libraries in member states, granting stipends to librarians, purchasing books and equipment for member libraries, and investigating issues in modern librarianship.